STUDI ZINK OKSIDA SEBAGAI KOMPOSIT BIOPLASTIK GENUS METROXXLEN, Sp DENGAN METODE MELT INTERCALTION (Lantanida Journal, 2020)
Bioplastic is one step to reduce the use of plastics that are not environmentally friendly. The genus Metroxxlen, Sp is a bioplastic material that is easily degraded in the soil. Metroxxlen, Sp has a hydrophilic nature which results in its physical properties being low. Bioplastic Starch Genus Metroxxlen, Sp is made by mixing ZnO as a reinforcement, Genus starch Metroxxlen, Sp as a source of natural polymers, with the addition of glycerol as a plasticizer. The results of the spread of ZnO in bioplastics can be seen with SEM. Comparison of ZnO with Genus Metroxxlen Sp. starch 1-3% wt produced a strengthened mechanism characteristic from 0.40 kg/cm2 to 0.70 kgf /cm2; the change in the extension changed down from 120.4% to 99.00%. For glycerol composition with variations from 1-3% wt, the change in elongation changes to increase from 90.00% to 98.00%, the nature of the mechanism changes to decrease from 0.25 kg/cm2 to 0.20 kgf /cm2.